Market Volatility and Equity Risk Factors: Dynamic Interac‎tions, Implications, and Evidence from India - Dutta, Kuntal; Singh, Kriti Bhaswar (International Journal of Accounting and Economics Studies, 2025)
This study examines the influence of investor sentiment, as captured by the India VIX, in conjunction with the Fama-French factors and ‎Carhart’s momentum factor, on equity risk premia in the Indian stock market. By focusing on periods of heightened uncertainty, specifically ‎the subprime crisis and the COVID-19 pandemic, the research explores how market volatility and risk factors interact to shape stock returns. ‎Using Granger causality tests, the analysis uncovers directional relationships between the India VIX and various equity risk premia, while ‎Impulse Response Functions and Variance Decomposition are employed to understand shock transmission and the sources of volatility ‎among factors. The findings indicate strong interconnectedness between market volatility (VIX) and key risk factors, particularly the market ‎risk premium and momentum. Notably, the study identifies a bidirectional causality between the size and market risk premia, emphasizing ‎the pivotal role of the size factor during periods of increased volatility. Variance decomposition results further reveal that, although risk ‎premia are predominantly influenced by their own shocks, there are modest interactions across different factors, underscoring the broader ‎influence of market sentiment. The results suggest that tracking market volatility can enhance portfolio adjustment strategies during turbulent ‎times. This research is limited to the Indian context and specific asset pricing factors, suggesting future studies should consider cross-country analyses and incorporate additional behavioral variables. Overall, the study provides new insights into the dynamic interplay be-‎tween investor sentiment and asset pricing, offering valuable guidance for investors, financial strategists, and policymakers aiming to better ‎understand and navigate periods of market stress‎.
Keywords: Asset Pricing Factors; Equity Risk Factors; Granger Causality; Impulse Response Function; India VIX